Improving Student Learning Outcomes in Energy Materials and Their Changes through Demonstrations, Concrete Media in Class V - Kristiawanto Kristiawanto (Universitas Sebelas Maret, 2020)
Based on the formulation of the problem, the research objective to be achieved through the application of concrete media-based methods is to improve science learning outcomes regarding the grouping of magnetic and non-magnetic objects in class V. This research was conducted at SDN 3 Jangkungharjo. The research was conducted in 2 cycles, where each cycle consisted of 4 stages of planning, implementing, observing / observing, and reflecting. The results of the pre-cycle research stated that: out of 32 students, only 10 students (31.25%) obtained complete learning. After the learning improvement process in cycle I, students who obtained learning completeness increased to 20 students (62.50%). The process of improving learning in Cycle II can improve students' understanding with learning outcomes reaching 30 students (93.75%). This increase shows that the methods used in the learning improvement process can be used as a means to improve student learning outcomes.